Evaluation of the antidiarrhoeal activity of Careya arborea leaves extract - Santosh Hadimani; H M Nanjappaiah; V P Patil; Shivakumar Hugar (Wolters Kluwer Medknow Publications, 2020)
Aim: To evaluate the antidiarrhoeal activity of Careya arborea leaves extract. Methods: Antidiarrhoeal activity of the methanol extract of Careyaarborea leaves (MECAL) was investigated using different animal models of diarrhea in rats. Results: The antidiarrhoeal activity demonstrated by MECAL was found to be dose-dependent at different doses in the castor oil-induced diarrhea model. Graded doses viz 125, 250 and 500 mg/kg produced a significant decrease in mean fecal drops, the weight of feces onset of diarrhea as compared with control. The % protection was found to be 35%, 40% and 51% at graded doses of extract respectively. In MgSO4 induced diarrhea model, test extract demonstrated dose-dependent antidiarrhoeal potential which was evident by monitoring significant delay in the onset of diarrhea and decrease in No. of fecal dropping and weight of stool when compared to the control group. The higher dose (500 mg/kg) of test extract produced 33 % protection of diarrhea which was found to be less potent than standard. Conclusion: The results of the present investigation concluded that the methanolic extract of Careyaarborea leaves (MECAL) demonstrated dose-dependent antidiarrhoeal activity due to the presence of pharmacologically effective component(s).